2006
DOI: 10.1136/bmj.38694.568981.80
|View full text |Cite
|
Sign up to set email alerts
|

Food buying habits of people who buy wine or beer: cross sectional study

Abstract: Objective To investigate whether people who buy wine buy healthier food items than those who buy beer. Design Cross sectional study. Setting Supermarkets in Denmark. Data Information on number, type of item, and total charge from 3.5 million transactions over a period of six months. Results Wine buyers bought more olives, fruit and vegetables, poultry, cooking oil, and low fat cheese, milk, and meat than beer buyers. Beer buyers bought more ready cooked dishes, sugar, cold cuts, chips, pork, butter or margarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 23 publications
4
91
1
1
Order By: Relevance
“…For example, wine drinkers make different dietary choices compared with beer or spirits drinkers 40 ; higher wine intake associates with a higher intake of healthy food items. 41 In conclusion, this intervention study confirms large-scale cross-sectional and prospective epidemiological studies that show regular moderate-to-heavy intake of alcohol raises BP in women. Our results provide no support for the concept that regular low-level alcohol intake can lower BP, suggesting that the J-shaped relationship between alcohol and BP in several studies is more likely because of the presence of unmeasured confounders.…”
Section: Discussionsupporting
confidence: 72%
“…For example, wine drinkers make different dietary choices compared with beer or spirits drinkers 40 ; higher wine intake associates with a higher intake of healthy food items. 41 In conclusion, this intervention study confirms large-scale cross-sectional and prospective epidemiological studies that show regular moderate-to-heavy intake of alcohol raises BP in women. Our results provide no support for the concept that regular low-level alcohol intake can lower BP, suggesting that the J-shaped relationship between alcohol and BP in several studies is more likely because of the presence of unmeasured confounders.…”
Section: Discussionsupporting
confidence: 72%
“…A study carried out in a French population showed that moderate alcohol drinkers or wine drinkers had better dietary habits and healthier behaviours compared to other drinkers or abstainers (Ruidavets et al, 2004). Additionally, a recent study conducted in Denmark showed that wine buyers made more purchases of healthy food items than people who routinely bought beer (Johansen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Odds ratios >1 indicate items purchased more commonly with beer. Reprinted with permission from Johansen D et al 25 drank red or white wine), and to a lesser extent beer, have a beneficial influence on cardiovascular mortality while spirits do not. This study was comprised of 45% men and 55% women, all between the ages of 30 and 70 y.…”
Section: Type Of Alcoholic Beverage Beer Wine and Spiritsmentioning
confidence: 99%